The role of TREM2 R47H as a risk factor for Alzheimer's disease, frontotemporal lobar degeneration, amyotrophic lateral sclerosis, and Parkinson's disease. Issue 12 (29th April 2015) - Lill, Christina M.; Rengmark, Aina; Pihlstrøm, Lasse; Fogh, Isabella; Shatunov, Aleksey; Sleiman, Patrick M.; Wang, Li‐San; Liu, Tian; Lassen, Christina F.; Meissner, Esther; Alexopoulos, Panos; Calvo, Andrea; et al.
Abstract: A rare variant in TREM2 (p.R47H, rs75932628) was recently reported to increase the risk of Alzheimer's disease (AD) and, subsequently, other neurodegenerative diseases, i.e. frontotemporal lobar degeneration (FTLD), amyotrophic lateral sclerosis (ALS), and Parkinson's disease (PD). Here we comprehensively assessed TREM2 rs75932628 for association with these diseases in a total of 19, 940 previously untyped subjects of European descent. These data were combined with those from 28 published data sets by meta‐analysis. Furthermore, we tested whether rs75932628 shows association with amyloid beta (Aβ42 ) and total‐tau protein levels in the cerebrospinal fluid (CSF) of 828 individuals with AD or mild cognitive impairment. Our data show that rs75932628 is highly significantly associated with the risk of AD across 24, 086 AD cases and 148, 993 controls of European descent (odds ratio or OR = 2.71, P  = 4.67 × 10 −25 ). No consistent evidence for association was found between this marker and the risk of FTLD (OR = 2.24, P  = .0113 across 2673 cases/9283 controls), PD (OR = 1.36, P  = .0767 across 8311 cases/79, 938 controls) and ALS (OR = 1.41, P  = .198 across 5544 cases/7072 controls). Furthermore, carriers of the rs75932628 risk allele showed significantly increased levels of CSF‐total‐tau ( P  = .0110) but not Aβ42 suggesting that TREM2 's role in AD may involve tau dysfunction.